PENGARUH BAHAN TAMBAH POTONGAN LIMBAH MATERIAL PLASTIK TERHADAP KUAT TEKAN BEBAS PADA TANAH LEMPUNG WATES - Muhammad Siddiqi Hajar, Dian Eksana Wibowo (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2014)
ABSTRACTThis research aims to classification clays in Kasongan Bantul based of AASTHO (AmericanAssociation of State Highway and Transportation Officials Classification) and to find out thehighest number of qu by using a mixed pieces of plastic material waste in percentage 0%,1%, 2%, and 3%. This research was conducted in laboratory soil mechanics the Departmentof Civil Engineering and Planning, Faculty of Engineering, Yogyakarta State University. Theresults showed that Clays in Kasongan Bantul based of AASTHO is classified A-7-6 (11) thatis medium to low; the plastic material waste reveals the highest number of qu, that is on 3 %that is 0,91286 kg/cm2; 2% that is 0,77660 kg/cm2; 1% that is 0,77354 kg/cm2; and 0% that is0,65345 kg/cm2.Keywords: Clay, plastic material waste, unconfined compression test